Política e violência em Merleau-Ponty - Zanfra, Beatriz Viana De Araujo [UNIFESP] (2019)
This thesis seeks to discuss, in the political work of Merleau-Ponty, the themes of politics and violence outside the schemes of alternatives that generally rule the debates on these themes. Since the phenomenological phase, we see that the great mark of Merleau-Pontian thought is precisely the radical refusal to think of being through alternatives such as subject and object, freedom and determinism, necessity and contingency, etc. Thus, with politics it is the same, so the question of being for or against the practice of violence in politics does not make much sense to our author, because from the moment we begin to read the classics of philosophy and political science and also study history, we see that violence has always been an indispensable element in the development of events. For this reason, a fundamental work of Merleau-Ponty is the recognition of this inextricable character of violence, politics and history. To this end, we have done this work against the backdrop of the author's phenomenological and ontological thinking, bringing the elements we deem necessary for a good dialogue with political themes. In this way, we initially discuss the phenomenology of the 1940s, particularly the issues of perception and freedom; we then move on to the topic of language studied in the 1950s; then, we move on to the study of the institution, addressed in the courses offered at Collège de France in the mid-1950s; and lastly we discuss the ontology developed in the posthumously published The Visible and the Invisible.